(untitled) (Medical Forum Monthly, 2022)
Objective: By research work to analyze the outcome of nicotine on the weight of developing embryo of chick and to estimate the safeguard effect in overcoming toxicity of nicotine by the leaves of green tea camellia sinensis. Study Design: A randomized control study Place and Duration of Study: This study was conducted at the Anatomy Department, HBS Medical and Dental College Islamabad, in association with Poultry Research Institute, Rawalpindi from June 2021 to November 2021. Materials and Methods: Forty eggs of Fayoumi species fertilized in nature of chick embryo were selected at zero hour of incubation. The research work was formulated by creating four distributive groups, each consisting of ten eggs. The G1 group was labelled as control group 1 administered with dose of 0.1ml of 9% Normal saline. Experimental G2 Injected with 0.1ml of 8% Camellia sinensis. Experimental G3 Injected with 0.1ml of 0.0001% Nicotine solution. Experimental G4 Injected with 0.1ml of 0.0001% Nicotine solution and 0.1 ml of 8% Camellia sinensis. After 17 days of incubation embryo were collected for measurement. Data were entered in a database using SPSS (Statistical Package for Social Science) version 25. Data were presented as tables. Chi-square test, Anova and PosthocTukey test were used for analyzing data. P value < 0.05 was considered significant. Results: The observations were made on the development of chick embryo by recording the weight of chick embryo and comparing with the control group and with each other. Data were entered and analysed using SPSS version 22. One-way analysis of variance (ANOVA) was used to compare weight of chick embryo among the different groups, p value of less than 0.05 was considered significant. Conclusion: It was concluded that Nicotine oxidative stress responsible for decreasing the developmental growth of chick embryo. Whereas green tea suppresses the oxidative stress but cannot reverse the effect.